Molecular characteristics and immune microenvironment of gastrointestinal stromal tumours: targets for therapeutic strategies - Yu, Yang; Yu, Mengdie; Luo, Lijie; Zhang, Zijing; Zeng, Haiping; Chen, Yan; Lin, Zeyu; Chen, Mengnan; Wang, Wei (Frontiers in Oncology, 2024)
Gastrointestinal stromal tumours (GISTs) are the most common mesenchymal tumours, arising mainly from the interstitial cells of Cajal (ICCs) of the gastrointestinal tract. As radiotherapy and chemotherapy are generally ineffective for GISTs, the current primary treatment is surgical resection. However, surgical resection is not choice for most patients. Therefore, new therapeutic strategies are urgently needed. Targeted therapy, represented by tyrosine kinase inhibitors (TKIs), and immunotherapy, represented by immune checkpoint inhibitor therapies and chimeric antigen receptor T-cell immunotherapy (CAR-T), offer new therapeutic options in GISTs and have shown promising treatment responses. In this review, we summarize the molecular classification and immune microenvironment of GISTs and discuss the corresponding targeted therapy and immunotherapy options. This updated knowledge may provide more options for future therapeutic strategies and applications in GISTs.